Do Capital Structure and Liquidity Increasing Value of The Firm? A Mediating Role of Profitability - Ni Luh Anik Puspa Ningsih; Putu Dyah Pradnya Paramitha (Universitas Warmadewa, 2019)
The aim of this study is to determine how profitability mediating the effects of the capital structure and company liquidity to company value. This research is conducted at the telecommunications sub-sector company on the Indonesia Stock Exchange (2015-2018). The population in this study are food and beverage companies in Indonesia Stock Exchange. Sample was conducted by purposive sampling method and then the number of samples is 12 companies. The research data is secondary data obtained from the website of the Indonesia Stock Exchange and the Indonesian Capital Market Directory from 2014 until 2017. Data analysis by path analysis technique. The results of this study that can be concluded are (1) the capital structure has negative insignificant impact on profitability, (2) the company liquidity has negative significant impact on profitability, (3) the capital structure has negative significant impact on value of the firm, (4) the company liquidity has negative insignificant impact on value of the firm, (5) the profitability had positive and significant impact on value of the firm, (6) profitability is able to mediate the effect of capital structure on value of the firm significantly, (7) the profitability is able to mediate the effect of company liquidity on value of the firm significantly.